Conceptual Metaphors of Love in The Capenters’Love songs / Nguyễn Thu Hà; NHDKH Dang Nguyen Giang, Ph. D. - Nguyễn, Thu Hà
Metaphor has been studied for a long time by many linguists. For traditional schools of linguistics, metaphor is merely a figure of speech used in literature. However, cognitive linguistics presents a different view of metaphor stating that metaphor is not only in literature but also pervasive in daily life language, and that it serves as a means of expressing thoughts as well as a vehicle of cognition that helps human beings recognize the world. This study give major views of metaphor in the light of cognitive linguistics such as: ontological metaphors, structural metaphors, orientational metaphors . Also, the study find out the conceptual metaphors patterns of Love in the Capenters’ love songs, discussing what mechanism helps language users to metaphorize an abstract concept (love) on the basis of another concept.